Deep Fungal Infection- An Emerging Problem in Bangladesh (Journal of Medicine, 2010)
Objective: Invasive deep fungal infections have become a major cause of morbidity and mortality over the pastthree decades. Organ transplantation, the use of aggressive chemotherapy and the availability and widespreaduse of immunosuppressive treatments for many medical ailments have resulted in large populations ofpatients who are at risk of fungal infections. We report our experience to increase awareness of the clinicalspectrum of disseminated fungal infection and its similarity to other infections and malignancy.Materials and Methods: Case reports from different medical institution for last 6 months were searched throughcase registry and recent scientific presentation and publications.Results: Recently a case of Histoplasmosis was reported in Dhaka Medical College Hospital (DMCH) wherea 57 years old male presented with low grade fever for 3 months, backache followed by progressiveweakness of both lower limbs , there was spastic paraplegia with sensory loss upto the level of D10. An openbiopsy from paravertebral soft tissue showed histopathological features consistent with histoplasmosis. Otherdeep fungal infections e.g. pulmonary blastomycoses, mucormycoses and pulmonary aspergilloma were alsoreported in DMCH and Bangabandhu Shiekh Mujib Medical University (BSMMU) and RMCH.Conclusion: As these fungal infections are not commonly encountered in our country and most of the disseminationhas similar clinical features of chronic inflammatory process and malignancy, we need a high index of suspicion todiagnose with different diagnostic approach. Bangladesh may be experiencing increase load of disseminated fungalinfections and awareness is now very important to explore its underlying aetiology.Keywords: Endemic mycoses; histoplasmosis; blastomycosis; mucormycosis; aspergilloma; BangladeshDOI: 10.3329/jom.v11i2.5466J MEDICINE 2010; 11 : 170-175